Strategi Guru Fiqih Untuk Meningkatkan Hasil Belajar Siswa dengan Metode True Or False di MA Bahrul ‘Ulum Tambakberas Jombang - Nisa’, Khoirun; Robbainah, Sofi Inayatur; Wahyudi (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Strategy is a way to obtain success in achieving certain goals. Apart from strategies, a method is also needed to facilitate an action. True or false is a collaborative activity with the characteristics of choosing a statement question between true or false, which can invite students to be involved with the learning material immediately. The true or false method needs to be used in Islamic jurisprudence learning to train students to learn or read so that they can master the material. Each student will express their opinion whether it is true or false regarding the statements they get so that students will easily require themselves to read and understand the material. jurisprudence learning. This research uses a descriptive qualitative method with data analysis carried out through triangulation, namely data condensation, data presentation and drawing conclusions. Based on observations made by researchers of MA Bahrul 'Ulum Tambakberas Jombang, researchers analyzed the need to improve student learning outcomes through a method or method so that students are not too passive in learning and are enthusiastic about improving literacy. The supporting factors are that students can more easily accept the material being taught, students can easily remember the material. This is because students are encouraged to think broadly and be responsible for their choices. By expressing his thoughts and opinions. So that the learning process can be effective and can learn optimally. Meanwhile, the obstacle factor lies in the students themselves in the sense that whether the students want to or not try to learn independently. However, teachers must also provide encouragement and support or ways to improve students so that they do not get bored and can understand the material so that they can improve student learning outcomes. The previous class conditions when students were studying fiqh looked passive and unenthusiastic, so this greatly affected student learning outcomes.